ENERGY EFFICIENCY CONDITION-BASED MAINTENANCE METHODOLOGY FOR COMPUTER ROOM AIR CONDITIONERS (2022)
A Computer Room Air Conditioner (CRAC) system has been modeled and simulated to set up a Condition-based maintenance strategy oriented on the equipment's energy efficiency performance (MCEE). The modeling was performed using ASPEN HYSYS based on actual performance conditions of a CRAC system in the Caribbean Colombia area. The condition-based was simulated based on a fouling model increase in the evaporator and condenser, decreasing the heat transfer process and increasing the heat loss. A 2-year fouling increase model was performed to obtain an economic - technical cost-function parameter and develop a cost-effective cleaning schedule for the evaporator and condenser. The results show a 5% COP decrease due to a fouling increase. The maintenance schedule for cleaning this system is cost-effective on the 310th day. Furthermore, a Critical Matrix of the CRAC performance is developed based on energy efficiency and a cost function. Copyright © 2022 by ASME.